2016
DOI: 10.1097/wnr.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of insulin-like growth factor-1 receptor and T type Cav3.2 channel in dorsal root ganglia in chronic inflammatory pain mouse model

Abstract: Insulin-like growth factor-1 (IGF-1) is a neurotrophic factor and plays important roles in the nervous system. Increasing evidence supports that IGF-1 contributes to pain hypersensitivity through its insulin-like growth factor-1 receptor (IGF-1R) by activating IGF-1R/Akt or MAPK signaling pathways, whereas T-type Cav3.2 channel can facilitate and amplify pain signals originating from the sensory periphery. A recent study showed that activated IGF-1R can increase T-type Cav3.2 channel currents and further activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…There is increasing evidence that Igf-1 contributes to pain hypersensitivity through binding to Igf-1r and activating Igf-1r–mediated PI3K, ERK, protein kinase B, or MAPK intracellular signaling pathways (53). Igf-1r is widely expressed in small, medium, and large DRG neurons (37, 54), and in chronic inflammatory and tissue injury models, Igf-1 signaling enhances thermal and mechanical hyperalgesia (54, 55). Moreover, inhibition of Igf-1r can reverse mechanical allodynia and thermal hyperalgesia in a rat model of cancer bone pain (36).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that Igf-1 contributes to pain hypersensitivity through binding to Igf-1r and activating Igf-1r–mediated PI3K, ERK, protein kinase B, or MAPK intracellular signaling pathways (53). Igf-1r is widely expressed in small, medium, and large DRG neurons (37, 54), and in chronic inflammatory and tissue injury models, Igf-1 signaling enhances thermal and mechanical hyperalgesia (54, 55). Moreover, inhibition of Igf-1r can reverse mechanical allodynia and thermal hyperalgesia in a rat model of cancer bone pain (36).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, IGF-1 does not only bind to TRPV2 channels but also to IGF-I receptors which are predominantly expressed in nociceptive neurons of sensory ganglia [36]. It has been reported that IGF-1 signaling via IGF-I receptors promotes the translocation of TRPV2 from intracellular pools towards the plasma membrane via phosphoinositide 3 (PI3) kinase activation in vitro; IGF-1-evoked Ca 2+ entry is consequently caused by TRPV2 activation [12,33,37].…”
Section: Discussionmentioning
confidence: 99%
“…This expression pattern is consistent with previous data showing abundant expression of Cav3.2 channels in small- to medium-sized TG neurons ( 25 , 41 ), while distinct from the broader distribution of Cav3.2 in rat DRG neurons ( 42 ). Cav3.2 channels were reported to be expressed exclusively in small DRG neurons in naïve mice ( 43 , 44 ); however, these results seem to be contradictory to those of most related studies. Increased expression of Cav3 isoform T-type channels in sensory neurons has shown functional diversity in distinct pain disorders ( 23 , 45 , 46 ).…”
Section: Discussionmentioning
confidence: 57%